Grid Database Design - Wells, April (CRC Press, 2009)
Grid Database Design investigates the origin, background, and components of this new computing model. This book presents new concepts and analyzes pre-existing ideas in the context of Grid, educating organizations as to how Grid can increase their computing power and strengthen their operations.